Analisis Pengaruh Tingkat Kepatuhan Wajib Pajak Restoran dan Pajak Hiburan Terhadap Pendapatan Asli Daerah Kota Pontianak - Pasorong, Dominique Putri Maharani; Grania Mustika, Ira; P. Karpriana, Angga (CV. Lafadz Jaya, 2024)
This study aims to analyze the impact of restaurant and entertainment tax compliance on Regional Original Income (PAD) in Pontianak City. Restaurant and entertainment taxes are key sources of local revenue that support the regional economy. Using a quantitative approach and secondary data, this research examines whether compliance levels in both sectors influence tax revenue and, in turn, contribute to PAD. The regression analysis results indicate that restaurant tax compliance has a significant impact on PAD, while entertainment tax does not. This suggests the importance of optimizing restaurant tax collection to boost PAD. The study recommends local governments enhance oversight, administrative systems, and outreach to taxpayers to increase compliance and local tax revenue.